Clinical efficacy of probiotic supplementation in the treatment of knee osteoarthritis: a meta-analysis - Miao Tian; Youyang Zhu; Shiyu Lu; Yuliang Qin; Xinyao Li; Tao Wang; Ying Guo; Hongling Shi; Dongdong Qin (Frontiers in Microbiology)
BackgroundWe aimed to systematically evaluate and analyze the clinical efficacy of oral probiotics in the treatment of knee osteoarthritis (KOA) based on the theory of “gut-joint axis.”MethodsWe searched PubMed, The Cochrane Library, Embase, China Knowledge Network (CNKI), Wanfang Database, and Wipro Database (CQVIP) databases for clinical randomized controlled trials of oral probiotics for the treatment of KOA. The literature was organized by Note express software, and the quality of the included literature was evaluated according to the Cochrane systematic evaluation method, and meta-analysis was performed using RevMan 5.4 software.ResultsFive randomized controlled trials with 694 participants were included in this study, and the results of the meta-analysis showed that the observation group experienced significant reductions in the Western Ontario and McMaster Universities Osteoarthritis Index total score, visual analog score, and high-sensitivity C-reactive protein level compared to the control group, but did not show significant differences in improvement of stiffness and regulation of body weight.ConclusionOral probiotics had an ameliorative effect on function, pain, and inflammatory response in patients with KOA, but our results need to be validated in future large-scale studies.Systematic review registrationThe website is https://www.crd.york.ac.uk/PROSPERO/.